Comparative performance assessment of plate heat exchangers with triangular corrugation. (August 2018) - Sharif, Asal; Ameel, Bernd; T'Jollyn, Ilya; Lecompte, Steven; De Paepe, Michel
Highlights: Triangular cross-corrugated plate with the largest apex angle, have the highest thermo-hydraulic performance. By increasing the apex angle both pressure drop and heat transfer coefficient increase. By increasing the apex angle, friction factor and the Colburn j factor follow two distinguished trends. The apex angles around of 90°–100° are the transitional angles for the flow regime. Peak of turbulence intensity, friction factor and Colburn j factor are observed around angles of 90°–100°. Abstract: A three-dimensional computational fluid dynamics approach with the Reynolds stress model is considered to investigate the influence of the apex angle on the thermal and hydraulic features of triangular cross-corrugated heat exchangers for a range of Reynolds numbers 310–2064. The influence of the intensity and complexity of the recirculation zones along with the turbulence intensity on those characteristics and corresponding viscous and pressure forces are studied. The choice of the computational domain as a unitary cell with periodic boundary condition versus a long channel with several cells is discussed. One on one comparison between the Reynolds stress model and experimental results shows less than 5% deviation, which is within the uncertainty of the experiment. By increasing the apex angle both pressure drop and heat transfer coefficient increase, due to the increase of the pressure force and the vorticity magnitude along the flow direction. The pressure force is the dominant force, contrary to pipe flow, where the viscous force is dominant. The influence of the apex angle on the friction factor and the Colburn j factor follows two distinguished trends. The apex angles around of 90°–100° are the transitional angles for the flow regime. Peak of turbulence intensity, friction factor and Colburn j factor are observed around these angles. The ratio between pressure and viscous forces decays after angle 100°, resulting in a smaller recirculation zone and lower turbulence intensity. Finally, the thermo-hydraulic performance of the considered geometries is compared with respect to each other based on a performance evaluation criterion. It is found that the geometry with the largest apex angle has the highest thermo-hydraulic performance.